Thin dielectric material for X5R type multilayer ceramic capacitor and preparation method of ceramic capacitor
By using the solid phase synthesis of BaTiO3-V2O5-Mn3O4-MgCO3-D2O3 system in multi-layer ceramic capacitors, a 'core-shell' structure is formed, which solves the deterioration of insulation resistance during thin-layer and miniaturization of multi-layer ceramic capacitors. and the problem of reduced reliability achieves high dielectric constant and good insulation, and meets the X5R standard.
Patent Information
- Application Number
- CN202411610847.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the process of thinning and miniaturization of existing multi-layer ceramic capacitors, there are problems of deterioration of insulation resistance and reduced reliability, especially in X5R type capacitors, which are difficult to maintain good dielectric temperature stability and high reliability.
The ceramic dielectric material is prepared by using the BaTiO3-V2O5-Mn3O4-MgCO3-D2O3 system. By adding submicron or nanoscale vanadium, magnesium, manganese, zirconium and other compounds and rare earth oxides to the barium titanate synthesized by the solid phase method, the Core-shell' structure inhibits oxygen vacancy migration and improves insulation characteristics to ensure high reliability of dielectric ceramic materials.
It achieves high dielectric constant, good insulation and high reliability of ceramic dielectric materials under small size and thin layering conditions, complies with the X5R dielectric material standards, and improves the temperature stability and insulation resistivity of the capacitor.
Smart Images

Figure CN119230291A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dielectric materials, and in particular to a thin dielectric material for an X5R type multilayer ceramic capacitor and a method for preparing the ceramic capacitor. Background Art
[0002] As an indispensable and important component in electronic devices, multilayer ceramic capacitors (MLCC) are widely used, in large quantities, and are irreplaceable. MLCC is widely used in electronic devices and components due to its small size, low dielectric loss, high insulation resistance, and excellent reliability. With the continuous innovation and development of 5G communications, electronic products, and new energy vehicles, the size of electronic components has gradually become miniaturized, which has placed higher and higher requirements on MLCC products, making today's MLCC gradually develop in the direction of low voltage, high capacitance, small size, and thin dielectric. However, as MLCC develops in miniaturization and thin dielectric layers, it is also necessary to meet the existing performance and reliability, which is undoubtedly a difficult problem that MLCC needs to face.
[0003] Multilayer ceramic capacitors are developing towards smaller size and thinner dielectric layers, making the dielectric layer thinner and the electrode ratio gradually increasing. The thinning of the dielectric layer reduces the number of grains on the single-layer dielectric, which reduces the reliability of MLCC. Therefore, it is crucial to study whether the thinning of the dielectric layer can improve the reliability of MLCC. For pure barium titanate (BaTiO3, BT) ceramic dielectrics, during the sintering process, Ti 4+ Will be restored to Ti 3+ , generating oxygen vacancy defects, which reduces the insulation and reliability of BT. With the rapid development of intelligent manufacturing and 5G technology, the demand for miniaturization and thinning of MLCC is increasing. In particular, X5R is one of the most widely used MLCCs. While maintaining good dielectric temperature stability (meeting EIA-X5R specifications), it has higher requirements for reliability and insulation resistance performance. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a thin dielectric material for X5R multilayer ceramic capacitors and a method for preparing ceramic capacitors to solve the problem of insulation resistance degradation and reliability degradation when existing dielectric ceramic materials tend to be thinner and smaller. The ceramic dielectric material of the present invention can maintain a good capacity change rate and a high dielectric constant, and can also ensure good insulation and high reliability.
[0005] Based on the above purpose, the present invention provides a thin dielectric material for X5R type multilayer ceramic capacitors, including a main component and an auxiliary additive, wherein the main component is barium titanate, and based on 100 parts by weight of barium titanate, the auxiliary additive includes the following raw materials in parts by weight: 0.08 to 1.5 parts by weight of zirconium oxide, 0.1 to 2.0 parts by weight of silicon dioxide, 0.2 to 0.7 parts by weight of magnesium carbonate, 0.01 to 0.06 parts by weight of manganese oxide, 0.02 to 1.5 parts by weight of vanadium oxide, and 0.1 to 3.5 parts by weight of rare earth oxide; wherein D in the rare earth oxide D2O3 is any one or more of Y, Ho, Yb, Gd, and Dy. If the auxiliary dopant does not contain the aforementioned composition, the dielectric ceramic material prepared cannot meet the X5R standard and good insulation resistance characteristics.
[0006] The present invention adopts BaTiO3-V2O5-Mn3O4-MgCO3-ZrO2-D2O3 system to prepare dielectric ceramic material, adds a small amount of submicron or nanometer-level vanadium, magnesium, manganese and zirconium compounds and two or more of yttrium, ytterbium and holmium element oxides to barium titanate synthesized by solid phase method, wet mixes them evenly, calcines them after drying to obtain dielectric ceramic material of MLCC, during the calcination process of dielectric ceramic, vanadium ions in the additive can inhibit other doping ions from entering into BaTiO3 grains, change the distribution of doping ions in the grains, thereby forming a "core-shell" structure, which can effectively inhibit the migration of oxygen vacancies, improve the insulation properties of ceramic dielectric, and finally ensure the reliability of MLCC; and manganese ions in the additive are variable valence elements (+2, +3) during the sintering process, which can replace B-site ions, thereby capturing oxygen vacancies. Rare earth element doping forms a core-shell structure. The construction of the core-shell structure in the grains helps to limit the migration of oxygen vacancies to the core of the grains in the early and middle stages of resistance degradation, thereby slowing down the overall insulation resistance degradation process of the medium.
[0007] In the raw materials of the thin dielectric material, barium titanate accounts for 80-92wt% of the total raw material, and the amount of the secondary additive accounts for 8-20wt% of the total material.
[0008] The raw materials of the thin dielectric material include 0.5 to 5 parts by weight of dispersant and 5 to 15 parts by weight of binder. The dispersant of the present invention is not particularly limited, but in order to achieve the above-mentioned dispersion purpose, the dispersant can be polyethylene oxide resin and other resins. The binder of the present invention is not particularly limited, but in order to achieve the above-mentioned bonding purpose, the binder can be polyvinyl acetal resin and other resins.
[0009] A thin dielectric material for X5R type multilayer ceramic capacitors. The first step is to mix and grind barium titanate, auxiliary additives, and dispersants using a solid phase method to obtain a powder mixture; the second step is to add a binder and a specific solvent to the above powder mixture to form a ceramic slurry; the binder of the present invention is not particularly limited, but for the purpose of achieving the above-mentioned bonding, the binder can be polyvinyl acetal resin and other resins.
[0010] A method for preparing an X5R multilayer ceramic capacitor comprises the following steps:
[0011] S1, barium titanate, auxiliary additives and dispersant are mixed and ball-milled to obtain a mixture;
[0012] S2, adding a dispersant and a binder to the mixture to form a ceramic slurry;
[0013] S3, casting;
[0014] S4, silk screen printing;
[0015] S5, lamination;
[0016] S6, lamination;
[0017] S7, cutting;
[0018] S8, glue removal;
[0019] S9, sintering;
[0020] S10, chamfering;
[0021] S11, copper plating;
[0022] S12, burning attachment;
[0023] S13. After electroplating, an X5R type multilayer ceramic capacitor is obtained.
[0024] The ball mill in S1 uses 0.1-0.5 mm zirconium oxide balls, the ratio of zirconium balls to dispersant is 1:4, the grinding speed is 1300-1800 rpm / min, and the grinding time is 300-500 min.
[0025] In the sintering process in S9, the sintering temperature is 1200-1300° C., the sintering atmosphere is 0.5-3.0% H2-N2, and the sintering time is 1.0-5.0 hours.
[0026] The sintering temperature is 1250° C., the sintering atmosphere is 2.0% H 2 —N 2 , and the sintering time is 80 min.
[0027] In the first step, barium titanate, auxiliary additives and dispersants are mixed and ground. The dispersant is used to disperse the main components and auxiliary additives in the dielectric ceramic material. The dispersant can be polyethylene oxide resin and other resins. Based on 100 parts by mass of BaTiO3, the amount of dispersant added is 0.5-5wt%. The grinding is carried out using a bedroom bead mill, the grinding ball is 0.1-0.5mm zirconium oxide ball, the ratio of zirconium ball to solvent is 1:4, the grinding speed is 1300-1800rpm / min, and the grinding time is 300-500min.
[0028] The second step is to add a binder and a dispersant to the powder mixture to form a ceramic slurry. Based on 100 parts by weight of BaTiO3, the amount of the binder added is 5 to 15 wt%. The dispersant of the present invention includes but is not limited to water, ethanol or toluene.
[0029] The third step, the fourth step, the fifth step, the sixth step, the seventh step and the eighth step of the present invention are common processes in the industry, and those skilled in the art can understand the practices of each step without detailed description of the present invention.
[0030] In the ninth step, the capacitor after debinding is sintered into porcelain to improve its compactness. During the sintering process, the sintering temperature is 1200-1300°C, the sintering atmosphere is 0.5-3.0% H2-N2, and the sintering time is 1.0-5.0 hours. Preferably, the sintering temperature is 1250°C, the sintering atmosphere is 2.0% H2-N2, and the sintering time is 80 minutes.
[0031] The tenth step, the eleventh step and the twelfth step of the present invention are common processes in the industry, and those skilled in the art can understand the practices of each step without detailed description of the present invention.
[0032] Beneficial effects of the present invention:
[0033] The present invention adopts BaTiO3-V2O5-Mn3O4-MgCO3-D2O3 system to prepare ceramic dielectric material, and adds a small amount of submicron or nanometer-level silicon, magnesium, manganese, vanadium compounds, and two or more of yttrium, ytterbium, and holmium element oxides to barium titanate synthesized by solid phase method, and wet-mixes them uniformly. During the sintering process, vanadium ions in the auxiliary additives can reduce the entry of D and Mg doping ions into BaTiO3 grains, thereby helping to form a "core-shell" structure; manganese ions in the additives are variable valence elements (+2, +3) during the sintering process, which can replace B-site ions, thereby capturing oxygen vacancies. By optimizing the additives, the temperature characteristics of dielectric ceramics are improved, and the temperature stability thereof meets the X5R dielectric material standard formulated by the American Electronic Industry Association.
[0034] For small-size and thin-layer manufacturing processes, oxygen vacancies will migrate intracrystalline and transcrystalline during the MLCC test phase, and finally oxygen vacancies will gather in the cathode region, forming a semiconductor layer structure with poor conductivity. By optimizing pure BaTiO3 powder, its oxygen vacancy migration is suppressed and enriched, thereby improving BT insulation. The present invention complies with the formula of X5R dielectric porcelain and has good insulation resistivity and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is the MLCC preparation process of the present invention. DETAILED DESCRIPTION
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0038] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.
[0039] Example 1
[0040] The preparation method of the dielectric material of this embodiment is carried out according to the following steps:
[0041] 1. 100 parts by weight of the main mixture powder (BaTiO3), as well as auxiliary additives such as ZrO2, SiO2, MgCO3, Mn3O4, V2O5, D2O3, etc. are added according to the proportion (the material selection is referred to Table 1, and the material mixing ratio is shown in Table 2), and 2% by weight of polyethylene oxide is added as a dispersant, and then ground using a bedroom bead mill for 5 hours to obtain a powder mixture, and then 8% by weight of PVB (polyvinyl butyral resin) binder is added to the powder mixture, and after uniform mixing, a slurry is obtained, and the slurry is made into a dielectric embryo membrane sheet through a casting machine, and then the nickel electrode slurry is printed by a screen printer. According to the design layer number requirements, the dielectric diaphragm and the printed electrode are alternately stacked to form a raw embryo laminate. The cut capacitor is subjected to a 3h debinding treatment at 300°C, and then sintered in a reducing atmosphere at 1250°C to form a ceramic body. Thereafter, chamfering, copper plating, sintering, and electroplating are performed in sequence to obtain a multilayer ceramic capacitor MLCC.
[0042] Examples 2-9 and Comparative Examples 1-5 were all manufactured in a similar manner to Example 1. The difference is that the dosage of the dopant was changed in Examples 2-9 and Comparative Examples 1-5. The specific conditions and evaluation results are shown in Table 2 below.
[0043] Table 1: Selection of raw powder used
[0044] serial number Raw material name Particle morphology Particle size specification 1 <![CDATA[Solid-phase method BaTiO3]]> Spherical or quasi-spherical 100-300nm 2 <![CDATA[MgCO3]]> Spherical or quasi-spherical 50-100nm 3 <![CDATA[SiO2]]> Spherical or quasi-spherical 50-80nm 4 <![CDATA[ZrO2]]> Spherical or quasi-spherical 50-100nm 5 <![CDATA[Mn3O4]]> Spherical or quasi-spherical 50-100nm 6 <![CDATA[V2O5]]> Spherical or quasi-spherical 50-100nm 7 <![CDATA[D2O3]]> Spherical or quasi-spherical 50-100nm
[0045] Table 2: Test ingredients
[0046]
[0047]
[0048] Examples 2-9 and Comparative Examples 1-5 were sintered into ceramic bodies in a reducing atmosphere at 1250°C, and Cu terminal electrodes were sealed at both ends of the sintered ceramic bodies, and the ends were sintered in a protective atmosphere to obtain multilayer ceramic capacitors MLCC. The MLCC samples were made with a dielectric thickness of 1.25 μm, a dielectric layer number of 255, and a specification of 0402.
[0049] Dielectric performance test of the sample: Under the conditions of 1KHz and 1V, the capacitance and loss are measured by using a bridge, and the dielectric constant is calculated based on the capacitance and the screen factor; the insulation resistance IR is tested using an insulation resistance meter TH2683 at 100V and 25℃, and the test time is 60s; within the range of -55℃ to +85℃, the capacitance at each temperature is measured using a temperature characteristic coefficient (TCC) test box, and the capacitance change rate at each temperature is calculated based on the capacitance at 25℃ according to the formula (△C / C25). The results are shown in Table 3.
[0050] Table 3
[0051]
[0052] Referring to Table 3, it can be seen that the multilayer ceramic capacitor of the nickel electrode X5R type MLCC dielectric material of the present invention meets the EIAX5R standard at a temperature characteristic of -55°C to 85°C, has a dielectric constant ≥4500, has good insulation resistance, and has a high breakdown voltage and high reliability.
[0053] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A thin dielectric material for X5R type multilayer ceramic capacitor, comprising a main component and an auxiliary additive, characterized in that: The main component is barium titanate. Based on 100 parts by weight of barium titanate, the auxiliary additives include the following raw materials in parts by weight: 0.08 to 1.5 parts by weight of zirconium oxide, 0.1 to 2.0 parts by weight of silicon dioxide, 0.2 to 0.7 parts by weight of magnesium carbonate, 0.01 to 0.06 parts by weight of manganese oxide, 0.02 to 1.5 parts by weight of vanadium oxide and 0.1 to 3.5 parts by weight of rare earth oxide; wherein D in the rare earth oxide D2O3 is any one or more of Y, Ho, Yb, Gd and Dy.
2. The thin dielectric material for X5R type multilayer ceramic capacitor according to claim 1, characterized in that: In the raw materials of the thin dielectric material, barium titanate accounts for 80-92wt% of the total raw material, and the amount of the secondary additive accounts for 8-20wt% of the total material.
3. The thin dielectric material for X5R type multilayer ceramic capacitor according to claim 2, characterized in that: In the raw materials of the thin dielectric material, the dispersant is 0.5 to 5 parts by weight, and the binder is 5 to 15 parts by weight.
4. A method for preparing an X5R type multilayer ceramic capacitor, characterized in that: The steps include: S1, barium titanate, auxiliary additives and dispersant are mixed and ball-milled to obtain a mixture; S2, adding a dispersant and a binder to the mixture to form a ceramic slurry; S3, casting; S4, silk screen printing; S5, lamination; S6, lamination; S7, cutting; S8, glue removal; S9, sintering; S10, chamfering; S11, copper plating; S12, burning attachment; S13. After electroplating, an X5R type multilayer ceramic capacitor is obtained.
5. The method for preparing the X5R type multilayer ceramic capacitor according to claim 4, characterized in that: The ball mill in S1 uses 0.1-0.5 mm zirconium oxide balls, the ratio of zirconium balls to solvent is 1:4, the grinding speed is 1300-1800 rpm / min, and the grinding time is 300-500 min.
6. The method for preparing the X5R type multilayer ceramic capacitor according to claim 4, characterized in that: In the sintering process in S9, the sintering temperature is 1200-1300° C., the sintering atmosphere is 0.5-3.0% H2-N2, and the sintering time is 1.0-5.0 hours.
7. The method for preparing the X5R multilayer ceramic capacitor according to claim 6, characterized in that: The sintering temperature is 1250° C., the sintering atmosphere is 2.0% H 2 —N 2 , and the sintering time is 80 min.
Citation Information
Patent Citations
Dielectric material of multilayer chip ceramic capacitor, and preparation method thereof
CN113880569A
Ceramic dielectric capacitor with high dielectric constant and high reliability, ceramic material prepared based on particle size combined substrate and preparation method of ceramic material
CN117902894A